Pug dog thoracolumbar myelopathy - Brander, Gustaf (Uppsala University, 2023)
The datasets consist of genotype data from pug dogs in plink format used for the study Multiple genetic loci associated with pug dog thoracolumbar myelopathy.

PDM plink files are QC:ed (--maf 0.01 --geno 0.05 --mind 0.05 and --hwe 1e-10) and relatedness filtered at a threshold of 0.177, including 89 dogs of which 51 were affected by pug dog thoracolumbar myelopathy and 38 were unaffected controls.

Genotyping technique is indicated in the FIID column, with GC indicating Gencove low-pass sequenced dogs using

Pipeline Dog low pass v2 with 676 dogs in the reference panel and GW indicating genotyped dogs using

Illumina 230k CanineHD BeadChip.

Chromosomal coordinates are based on the dog CanFam3.1 genome assembly.
Keywords: Gene mapping; Medical and Health Sciences; Medicin och hälsovetenskap; Genetics and Genomics; Genetik och genomik